Analisis al-nabr pada bagian mujamalah hingga penyebutan judul dalam khitobah berbahasa arab: kajian fonetik terapan. - Najwa, Ummu Qathrun (Maliki Interdisciplinary Journal, 2026)
This study examines the phenomenon of al-nabr (sound emphasis) in the opening segments of khitobah, particularly in the mujammalah section up to the mention of the title. The research focuses on (1) describing the patterns of nabr that appear in each opening section, (2) identifying points of emphasis on words that have a rhetorical function, and (3) explaining how variations in pitch and duration shape the prosodic character of khitobah. The research data consists of recordings of the author’s khitobah with a duration of ±2 minutes. The analysis was carried out using a prosodic descriptive method by listening to the recordings intensively and annotating pitch rises (↑), pitch falls (↓), and emphasis on certain words or phrases.The results show different patterns of emphasis in each part of the opening. Mujammalah is dominated by a rising pitch contour to create an impression of respect, salam displays strong emphasis as a marker of transition, muqaddimah shows a more stable pattern of emphasis with a low pitch, while the mention of the title shows a peak of emphasis as a form of affirmation of the main theme. These findings confirm that variations in nabr and pitch play an important role in shaping the rhetorical power of khitobah, and have implications for the development of Arabic vocal learning and prosody training.